The Effectiveness of Spotify in Improving English Vocabulary through Song Lyrics - Jannah, Miftahul; Zahra, Maulisa; Yusnida, Dara (English Teaching and Linguistics Journal (ETLiJ), 2026)
This study investigated whether using Spotify improves students’ English vocabulary mastery, motivated by low vocabulary achievement and lack of interest in conventional methods. A quantitative pre-experimental design with one-group pre-test and post-test was employed. Participants were 22 eighth-grade students from MTs Keutapang Dua, selected through total sampling. Data were collected using vocabulary tests and a questionnaire on students’ responses to Spotify-based learning. Results showed an increase in vocabulary mastery by 12.75 points, with the mean pre-test score rising from 60.86 to 73.61 in the post-test. A paired sample t-test revealed a t-count of 28.84, exceeding the t-table value of 2.080 (df = 21, p 0.05), indicating a significant improvement. Questionnaire responses (M = 3.58, SD = 0.32) compared to the neutral midpoint of 2.5 yielded a very large effect size (Cohen’s d = 3.38), showing strongly positive perceptions. The highest-rated item (M = 3.9) was viewing lyrics while learning, while the lowest (M = 3.1) concerned difficulty understanding singers. In conclusion, integrating Spotify and English song lyrics effectively enhances vocabulary development and increases student motivation and interest. Teachers are encouraged to adopt music-based digital platforms as instructional strategies.